Level of perception of the sonic landscape and its connotation with the sonic identity in the district of Huánuco 2017 - Berrospi-Noria, Jean P. (2019)
The objective of the research was to know the degree of the level of perception of the local sonic landscape is associated to the sound identity in the citizens of the District of Huánuco 2017. The type of research was analytical. The research design was transactional - relational. The population was all citizens between 19 and 69 years of age in the district of Huánuco, with a population estimated to 461,564 in 2015, being a population with a relatively high number (greater than 100.00) to extract a sample in order to represent the local sonic identity of the district of Huánuco. The sample consisted of 384 citizens between 19 and 69 years old. To achieve the representativeness of the population centers of the jurisdiction of the district of Huánuco: Kotosh, Marabamba, Colpa Baja and Huánuco city, we will use the technique of sampling by  conglomerates. The overall results of the research were 53% of the respondents stated that YES vary in intensity during the day, natural and human activities, but 47% say NO. The conclusion was there is an intimate and close relationship between the level of sonic perception and the sonic identity in the citizens of the district of Huánuco because this research shows that the citizen interviewed is related to their sonic environment through the memory in past experiences as evidenced by the results.